A Coverage of Maternal Health Checks Before Discharge in Cambodia: A Population-Based Analysis of the 2021-22 Demographic and Health Survey: Evidence from the 2021–22 Cambodia Demographic and Health Survey - Sokha YEM (Indonesian Journal of Health Research and Development, 2026)
Abstract Background: The immediate postpartum period represents a critical window for preventing maternal morbidity and mortality. In Cambodia, facility delivery rates reached 93.9% by 2021-22, yet whether essential quality-of-care processes such as maternal health assessment before discharge are consistently implemented remains uncertain. This study aimed to estimate national coverage of maternal health checks before discharge and quantify missed opportunities among facility deliveries. Methods: We conducted a cross-sectional secondary analysis of the 2021-22 Cambodia Demographic and Health Survey (CDHS), including women aged 15-49 with a most recent live birth in the preceding 24 months (n=3,348 unweighted). The primary outcome was whether maternal health was checked before discharge. Weighted prevalence estimates with 95% confidence intervals (CI) were calculated overall and stratified by sociodemographic and delivery characteristics. Multivariable logistic regression identified factors associated with missed checks among facility deliveries. Results: Nationally, 91.0% of women (95% CI: 89.6-92.2) reported a maternal health check before discharge. Among the 93.9% who delivered in facilities, 91.0% received a check, leaving 9.0% as missed opportunities. Substantial geographic disparities were observed, with coverage ranging from 82.4% in some regions to 96.8% in others. Women with no education (adjusted OR=2.89, 95% CI: 1.45-5.76), rural residence (aOR=1.67, 95% CI: 1.12-2.49), and those in the poorest wealth quintile (aOR=2.34, 95% CI: 1.34-4.09) had significantly higher odds of missed checks. Primiparous women and those with delivery complications also experienced lower coverage. Conclusions: Despite near-universal facility delivery, nearly one in eleven women were discharged without documented maternal health assessment, with pronounced inequities by socioeconomic status, education, and geography. These findings reveal critical gaps in postpartum quality of care that disproportionately affect vulnerable populations. Strengthening standardized discharge protocols, enhancing staff accountability through integrated checklists and supervision, and prioritizing equity in service delivery are essential to ensure consistent, high-quality postpartum care for all women. Keywords: Cambodia; Demographic and Health Survey; postpartum care; quality of care; health equity; maternal health; discharge assessment